Impact of cardiovascular disease and risk factors on fatal outcomes in patients with COVID-19 according to age: a systematic review and meta-analysis - Bae, SungA; Kim, So Ree; Kim, Mi-Na; Shim, Wan Joo; Park, Seong-Mi (Heart (British Cardiac Society), 2021)
ObjectivePrevious studies that evaluated cardiovascular risk factors considered age as a potential confounder. We aimed to investigate the impact of cardiovascular disease (CVD) and its risk factors on fatal outcomes according to age in patients with COVID-19.MethodsA systematic literature review and meta-analysis was performed on data collected from PubMed and Embase databases up to 11 June 2020. All observational studies (case series or cohort studies) that assessed in-hospital patients were included, except those involving the paediatric population. Prevalence rates of comorbid diseases and clinical outcomes were stratified by mean patient age in each study (ranges: <50 years, 50–60 years and ≥60 years). The primary outcome measure was a composite fatal outcome of severe COVID-19 or death.ResultsWe included 51 studies with a total of 48 317 patients with confirmed COVID-19 infection. Overall, the relative risk of developing severe COVID-19 or death was significantly higher in patients with risk factors for CVD (hypertension: OR 2.50, 95% CI 2.15 to 2.90; diabetes: 2.25, 95% CI 1.89 to 2.69) and CVD (3.11, 95% 2.55 to 3.79). Younger patients had a lower prevalence of hypertension, diabetes and CVD compared with older patients; however, the relative risk of fatal outcomes was higher among the former.ConclusionsThe results of the meta-analysis suggest that CVD and its risk factors (hypertension and diabetes) were closely related to fatal outcomes in COVID-19 for patients across all ages. Although young patients had lower prevalence rates of cardiovascular comorbidities than elderly patients, relative risk of fatal outcome in young patients with hypertension, diabetes and CVD was higher than in elderly patients.Prospero registration numberCRD42020198152.